2008
DOI: 10.1029/2007ja012843
|View full text |Cite
|
Sign up to set email alerts
|

Formation of maximum electric potential at the geomagnetic equator by the disturbance dynamo

Abstract: [1] The effect of a disturbance dynamo during geomagnetic activity on the equatorial ionospheric electric fields is investigated, using model results from the NACR/TIEGCM (National Center for Atmospheric Research Thermosphere Ionosphere Electrodynamics General Circulation Model). Model runs are made for different time-lengths of geomagnetic activity, for different seasons, and for different solar activities to investigate how and where the maximum electric potential forms. Model results show that the maximum e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 21 publications
5
66
0
Order By: Relevance
“…The geomagnetic storm can initiate ESF in the post midnight sector because of abnormal upward reversals in the vertical plasma drift under the action of eastward electric fields of ionospheric disturbance dynamo (IDD) [Kelley and Maruyama, 1992;Hysell and Burcham, 1998] and also often because of penetration of eastward electric fields associated with northward turning of IMF Bz . There are ample of studies reported which explain the development/inhibition of ESF during geomagnetic storm and the role of storm time perturbation electric fields during last three decades [Aarons, 1991;Sastri et al, 1993;Abdu et al, 1995;Fejer et al, 1999;Basu et al, 2001bBasu et al, , 2005Sobral et al, 2001;Huang et al, 2005, Huang andChen, 2008;Tulasi Ram et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…The geomagnetic storm can initiate ESF in the post midnight sector because of abnormal upward reversals in the vertical plasma drift under the action of eastward electric fields of ionospheric disturbance dynamo (IDD) [Kelley and Maruyama, 1992;Hysell and Burcham, 1998] and also often because of penetration of eastward electric fields associated with northward turning of IMF Bz . There are ample of studies reported which explain the development/inhibition of ESF during geomagnetic storm and the role of storm time perturbation electric fields during last three decades [Aarons, 1991;Sastri et al, 1993;Abdu et al, 1995;Fejer et al, 1999;Basu et al, 2001bBasu et al, , 2005Sobral et al, 2001;Huang et al, 2005, Huang andChen, 2008;Tulasi Ram et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…We also see that the magnitudes of the poleward penetration electric fields decay very fast from high latitudes to low latitudes in the southern hemisphere, but some contributions may come from the effect of the local time dependence. These westward plasma drifts presumably result from the penetration electric fields because the meridional electric fields associated with the disturbance dynamo in the daytime are very small as compared with the drift values shown in Figure 5a [ Huang and Chen , 2008], which will be demonstrated in section 3.…”
Section: Data Description and Analysismentioning
confidence: 99%
“…A interesting result revealed from the model run is the nighttime meridional electric field raises to a very large value (e.g., 5.6 mV/m in Figure 7) during the intense storm period, but the maximum magnitude for the eastward zonal component is only up to about 2 mV/m at 0500 LT, where appears the maximum eastward electric field in the storm time [ Scherliess and Fejer , 1997; C.‐M. Huang et al , 2005; Huang and Chen , 2008]. It explains why the westward plasma drifts can be easier seen than the upward/poleward plasma drifts in the nighttime, as shown in Figures 1a and 1b, Figures 3a and 3b and Figures 5a and 5b.…”
Section: Model Simulation Of the Disturbance Dynamo Electric Fieldmentioning
confidence: 99%
See 2 more Smart Citations